Resilience and Reflections: A Study of Chinese Cinema in the Wake of Global Challenges and Socio-Political Shifts - Changsong Wang; Lucyann Kerry; Xiaotian Gao (SAGE Open)
The Chinese film industry has undergone significant transformations, particularly amidst the backdrop of the COVID-19 pandemic and global socio-political shifts. This evolution encompasses a complex interplay between tradition and modernity, state control versus artistic freedom, and China’s burgeoning global ambitions. This study examines diverse elements of film production, commercialization, and the nuanced dynamics of both domestic and international box-office performance, specifically focusing on the pivotal year of 2023—a juncture marked by global events intersecting with domestic geopolitical landscapes. Domestically, the Chinese government further refined its media and cultural policies, strategically shaping the framework for film production, distribution, and international collaborations. During this period, Chinese studios intensified their efforts to balance commercial viability with culturally embedded storytelling, aiming to engage both domestic and global audiences effectively. Through a problem-centered interview approach with nine Chinese scholars recognized as leading figures of film studies in China, this study aims to provide a comprehensive understanding of the industry in 2023. Their engagement with the inquiry process and the subsequent interview results offer what may be a new and comprehensive depth of understanding to the Chinese film industry. This may lay a new foundation for better understanding the marked disparity between locally acknowledged Chinese box office successes and the substantial divergence from Hollywood’s pervasive influence.